Coworking Space and Library with a Humanist Architectural Approach - Hangin, Afra Akwila; Setyowati, Wiwit; Purnomo, Andi; Pratiwi, Isna (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
Semarang City is one of the big cities, of course, has a population growth rate that increases every year. To improve the quality of the needs of community activity spaces, we currently need a container that can accommodate individual and group activities. Coworking Space and Library is a building that was built to be a social and informative forum for the community, especially in Semarang City. The Coworking Space and Library was built to overcome the decline in the level of reading and social life of the community using the Humanist Architecture Approach, it is hoped that this can give the impression of safety and comfort and function as expected. The method used is the descriptive method, carried out by collecting and analyzing data to obtain planning and design concepts. The Humanist Architecture Approach prioritizes the five basic human needs according to Abraham Maslow and the elaboration of the theory by Jhon Lang, namely Physiological Needs, Safety Needs, Belonging Needs, Esteem Needs, and Self Actualization Needs. The application of this theory can solve the problem of the achievement of the Coworking Space and Library building in Semarang City.